Neural processing of lower- and upper-case text in second language learners of English: an fMRI study. Issue 2 (7th February 2018) - Choi, Sungmook; Jang, Kyung Eun; Lee, Yoonhyoung; Song, Huijin; Cha, Hyunsil; Lee, Hui Joong; Oh, Ah-Gyeong; Kang, Hyunah; Kim, Yang-Tae; Chang, Yongmin
ABSTRACT: Upper-case text is considered detrimental to the reading comprehension of second language learners of English. Little is known about the neurocognitive mechanisms underlying the processing of upper-case text. To investigate this issue, Korean students ( n = 23) performed 40 reading trials, and their reading comprehension of text written in either upper- or lower-case letters was recorded while their brain activities were scanned with functional magnetic resonance imaging. Compared to lower-case text, upper-case text elicited greater activation of the primary visual areas in both hemispheres associated with orthographic processing. In contrast, lower-case text increased neural activity in brain regions associated with higher-order reading comprehension processes (e.g. the integration of text information) and the premotor cortex. Collectively, based on automacity theory, these results suggested that upper-case text interferes with reading comprehension because it requires increased orthographic processing, which in turn leaves fewer neural resources for phonological processing and higher-order reading comprehension processes.